Exploring Children's Character Education through the Moral Teachings of Raden Mas Panji Sosrokarton - Fatimatul Zuhroh (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2022)
This research examines Sosrokartono's teachings that involve the harmony of human relationships with God and fellow creatures. These teachings align with the values of Pancasila as the foundation of the state and reflect the character of education. This literature research uses a qualitative method with interpretation, abstraction analysis, and verstehen. The results show that Sosrokartono's moral teachings are practical and humanist. The practical nature is reflected in daily examples, while the humanist nature invites humans to help others with love and devotion to God. These teachings align with the main values of character building, including religion, nationalism, independence, cooperation, and integrity. In conclusion, Sosrokartono's teachings have strong relevance to character education and the values of Pancasila.